Efficacy and Safety of SID142 in Patients With Peripheral Arterial Disease: A Multicenter, Randomized, Double-Blind, Active-Controlled, Parallel-Group, Phase III Clinical Trial - Kook, Hyungdon; Yu, Cheol Woong; Choi, Donghoon; Ahn, Tae Hoon; Chang, Kiyuk; Cho, Jin-Man; Kim, Soo-Joong; Park, Chang Gyu; Cho, Deok-Kyu; Kim, Sang-Hyun; Lee, Han Cheol; Jin, Han-Young; et al. (Clinical therapeutics, 2022)
Renexin® is a combination pill of cilostazol and Ginkgo biloba leaf extract that is used for the improvement of ischemic symptoms associated with peripheral arterial disease (PAD). SID142 is a controlled-release tablet of cilostazol (200 mg) and G biloba leaf extract (160 mg) that was developed to address the limitation of BID administration with Renexin. This study aimed to verify that SID142 was not inferior to Renexin in the treatment of patients with PAD. This was a multicenter, randomized, double-blind, active-controlled, parallel-group, Phase III clinical trial. Study subjects were randomized to receive SID142 once daily or Renexin twice a day for 12 weeks. The primary end point was a change in the patient assessment of lower leg pain intensity with the use of a visual analog scale (VAS) after 12 weeks of treatment. If the lower limit of the two-sided 95% CI was greater than –10, the study drug was declared noninferior to the reference drug. Secondary efficacy end points included cold sensation, ankle-brachial index, ankle systolic pressure, maximum walking distance, pain-free walking distance, and investigator's global assessment. Study group results were compared 4, 8, and 12 weeks after treatment. Adverse events were assessed as a safety end point. In total, 344 subjects from 19 medical centers were screened, and a total of 170 subjects were randomly assigned to either the SID142 (n = 86) or the Renexin (n = 84) group. Analysis of the change in lower extremity pain at 12 weeks compared with baseline revealed that SID142 was not inferior to Renexin (21.44 [19.23] vs 22.30 [17.75]; 95% CI, –7.70 to 5.97; P = 0.5942). No significant differences were found between groups in any secondary efficacy end point. However, the incidence of adverse reactions was significantly lower in the SID142 group (22.35% vs 39.29%; P = 0.0171). SID142 once daily was not inferior to Renexin twice a day for efficacy in patients with PAD. SID142 had a favorable safety profile. ClinicalTrials.gov identifier: NCT03318276.